Answer:
1) x=9
edit:
2) x=25
Step-by-step explanation:
Since all angles added together in any triangles is 180,
we can conclude that
180=(7x-1)+(5x+2)+(7x+8)
solving for x:
180=19x+9
180-9=19x
171=19x
x=9
Edit:
2)since we are given the outside angle we have to find the inside one first before finding the other angles, a straight line is 180 degrees aswell, so 180-(3x-10) would give you the inside angle in terms of x
so adding them all together again should ewual 180:
180=(180-(3x-10))+25+(x+15)
180=180-3x+10+25+x+15
0=-2x+50
2x=50
x=25
we know that
therefore
the answer is
No 6.2 could be put as 6.20 and 1.75
6 is bigger than 1
A. y=2x + 6/5
B. y= 5/6x +2
C. y=2x + 5
D. y=6/5x + 2
Answer: The correct answer is D.
Step-by-step explanation:
The easiest way to compare fractions is by having a common denominator for both fractions.
This is because, when the denominator is the same in both fractions, we will simply compare the numerators and the greater fraction will be the one having greater numerator
Part 1:
The first given fraction is
The second given fraction is
We can make the denominator in the second one equal to 12 by multiplying it by 4.
However, to preserve the value of the fraction, we will multiply it by
This will give us:
* =
Now, the two fractions became and
The denominator is the same, so we will compare numerators.
Since 7 is greater than 4, therefore:
is the greater fraction
Part 2:
The first given fraction is
The second given fraction is
We can make the denominator in the second one equal to 12 by multiplying it by 4.
However, to preserve the value of the fraction, we will multiply it by
This will give us:
* =
Now, the two fractions became and
The denominator is the same, so we will compare numerators.
Since 8 is greater than 7, therefore:
is the greater fraction
Hope this helps :)
The value of b that makes x-2 a factor of x² - bx + b is 4.
Polynomial is an expression involving the operations of addition, subtraction, multiplication of variables.
Types of polynomials are quadratic, linear, cubic and so on.
The factor theorem states that; when f(k) = 0, then (x – k) is a factor of f(x).
Given that x-2 is a factor of x² - bx + b, hence:
f(2) = 2² - b(2) + b = 0
4 - 2b + b = 0
b = 4
Therefore the value of b that makes x-2 a factor of x² - bx + b is 4.
Find out more at: brainly.com/question/2449381
we have that
we know that
If is a factor of
then
for
is equal to zero
so
therefore
the answer is
the value of b is equal to